Determinants and health outcomes of trajectories of social mobility in Australia - Mithilesh Dronavalli; Andrew Page; Sandro Sperandei; Gabriela Uribe; Carmen Huckel Schneider; John Eastwood (Elsevier, 2023)
Objectives: To investigate trajectories in socio-economic position (SEP) and the onset of a range of physical and mental health outcomes and commencement of treatment. Methods: The Household Income and Labour Dynamics Australia (HILDA) study, a nationally representative prospective cohort study over the period 2001 to 2020 was used to define trajectories of SEP. Trajectories of low, low-middle, upper-middle and high SEP and decreasing (low-middle to upper-middle SEP) or increasing (upper-middle to lower-middle SEP) SEP were identified using k-longitudinal means. Cox-regression was used to assess SEP trajectories and physical (arthritis or osteoporosis, any cancer, asthma, chronic bronchitis or emphysema, Type 1 diabetes, Type 2 diabetes, hypertension or high blood pressure, and coronary heart disease), and mental health (depression or anxiety) outcomes, and treatment commencement. Predictors of SEP trajectories were also investigated using multinomial logistic regression and random forests. Results: Decreasing SEP had a higher relative risk of new onset illness than increasing SEP for all health outcomes. Increasing SEP had relative risk estimates that were more consistent with upper-middle income groups and decreasing SEP had a relative risk consistent with lower-middle income groups. In contrast, there was no socio-economic gradient in treatment commencement for physical health outcomes, or depression or anxiety, with the exception of arthritis or osteoporosis. Conclusion: Decreasing SEP was associated with poor health outcomes, and increasing SEP with better health outcomes. A range of socio-demographic and psychosocial determinants of SEP trajectories were identified to inform policy responses that could modify trajectories of health inequalities in the Australian context.